Estimation of Toll-like receptor 9 in gingival tissues of patients with chronic periodontitis with or without hyperlipidemia and its association with the presence of Porphyromonas gingivalis - Narayan, Ipshita (J Indian Soc Periodontol, 2018)
BACKGROUND: Recent evidence suggests the interactions between bacterial DNA and nucleic acid receptors to play a role in inflammatory tissue destruction. The current study aims to evaluate the expression of Toll-like receptor 9 (TLR9) in periodontal disease associated with or without hyperlipidemia and to associate it with the presence of Porphyromonas gingivalis. MATERIALS AND METHODS: Thirty participants in the age range of 25–50 years were randomly recruited and divided into three groups, i.e., healthy (Group I), chronic periodontitis without hyperlipidemia (Group II), and chronic periodontitis with hyperlipidemia (Group III). The gingival tissue samples were analyzed for TLR9 using immunohistochemistry, and plaque samples were analyzed for P. gingivalis using polymerase chain reaction. RESULTS: The TLR9-positive cell ratio in gingival connective tissue for Group II and Group III was 0.95 ± 0.03 and 0.94 ± 0.03, respectively, which was significantly higher than that of Group I, with P < 0.001 (0.88 ± 0.04). These groups also demonstrated significantly higher presence of P. gingivalis as compared to Group I with P < 0.001. There was a positive association between TLR9 in gingival connective tissue and presence of P. gingivalis. CONCLUSION: The results of this study reveal a potential role of TLR9 in chronic periodontitis, in association with P. gingivalis. Furthermore, these variables do not show an appreciable change in hyperlipidemics suggesting a weak relation between TLR9 and lipid levels.